ACHIEVEMENT OF CHILDREN DEVELOPMENT THROUGH 2013 CURRICULUM IMPLEMENTATION IN ISLAMIC BASED KINDERGARTEN - Muhammad Azam Muttaqin (STAINU Purworejo, 2020)
This study aims to find out how much influence the 2013 Curriculum applied by Teachers to aspects of development in children. This study included all experimental studies that used a non-equivalent posttest only control group design. The study was located at TK An-Nur 3Yogyakarta. Data collection techniques using observation techniques, then the data collected were analyzed with descriptive statistics and t-test infirential statistics. The results of this study found that based on the t test on the relationship of teachers in applying the 2013 curriculum to the achievement of aspects of child development, it can be concluded that, based on the output of coefficients, the teacher variable regression coefficient (X1) is positive (+). So it can be said that the teacher in implementing Curriculum 2013 (X1) has a positive effect on aspects of child development (Y). The positive influence can be interpreted, the increasing competence of teachers in educating (implementing the 2013 Curriculum) (X1) then the aspect of child development also increases (Y). But when tested to find out whether the effect is significant or not, the results are contradictory then the regression coefficient values of the teacher variable (X1) are all insignificant, except the teacher's influence on the development of language aspects in children. With the value of t count 2.887> t table 2.228, it can be concluded that (H1) there is an influence (X1) on Y5.